Effects of Coconut Water, Benzylaminopurine, and Naphthalene Acetic Acid on Seed Germination and Rhizome Food Reserve: In Vitro Culture of Eulophia flava (Lindl.) Hook.f. - Ekarat Vasupen; Weenun Bundithya; Nuttha Potapohn* (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
ulophia flava (Lindl.) Hook.f. in Thailand has been threatened by agricultural deforestation and city expansion. Efficient seed propagation via tissue culture technique is necessary to enhance the conservation and utilization of this orchid. Thus, the effects of coconut water (CW), benzylaminopurine (BA), and naphthalene acetic acid (NAA) on seed germination and rhizome food reserve were studied. Capsules were collected at 180 days old following hand-pollination. Ten media; MS, MS + 10% CW, MS + 2.69 µM NAA, MS + 5.38 µM NAA, MS + 2.22 µM BA, MS + 4.44 µM BA, MS + 2.69 µM NAA + 2.22 µM BA, MS + 2.69 µM NAA + 4.44 µM BA, MS + 5.38 µM NAA + 2.22 µM BA, and MS + 5.38 µM NAA + 4.44 µM BA, were used for seed germination and seedling development. MS without supplements was found to be suitable for E. flava seed culture, with seed germination of 26.39%, survival of 100%, and seedling development in the post-protocorm stage of 11.50%. After that, seedlings in early stage 4 were selected from MS medium treatment and transferred to five media: MS, 1/2 MS, 1/2 MS macronutrient, MS + 10% CW and MS + 2.69 µM NAA, for formation and food reserves of rhizomes. Four months after being subcultured, seedlings in early stage 4 developed to late stage 4. Rhizome size and cuticle thickness showed no significant differences in all media. Seedlings in 1/2 MS macronutrient showed the highest rhizome food reserve (201.21 mg/g DW of TNC). Keywords: Eulophia flava; coconut water; plant growth regulators; food reserve; TNC *Corresponding author: Tel.: (+66) 813876776 E-mail: natorchid@gmail.com